PERAN LEMBAR KERJA PESERTA DIDIK (LKPD) KURIKULUM 2013 TERHADAP KEMANDIRIAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (Studi Deskriptif di Kelas IX SMP Negeri 10 Kota Serang) - Angraeni, Desti; Ria Yuni Lestari; Wika Hardika Legiani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Abstract: The purpose of this study was to describe the process of making the 2013 Curriculum LKPD in Pancasila and Citizenship Education subjects, to determine the role of the 2013 Curriculum LKPD in increasing the independence of students in Pancasila and Citizenship Education subjects, and to find out the obstacles to using the 2013 Curriculum LKPD in increasing independence. students in Pancasila and Citizenship Education lessons at SMP Negeri 10 Serang City. This study uses a descriptive method with a qualitative approach and data collection through the results of interviews, observations and documentation to the deputy principal of the curriculum, teachers, and students of Junior High School Number 10 of Serang City. The results of this study indicate that the process of making LKPD Curriculum 2013 in the subjects of Pancasila and Citizenship Education is carried out by conducting curriculum analysis, compiling a map of LKPD needs, determining the title of KPD, writing LKPD and determining assessment tools. There is a role for the 2013 Curriculum LKPD in increasing the independence of students' learning in the subjects of Pancasila and Citizenship Education, namely creating a condition where students have a competitive desire to advance for their own good, as a learning tool so that students are able to take decisions and take initiatives to deal with problems that arise. faced, as a tool to foster students' confidence in what they are doing. The obstacles faced by teachers and students in utilizing the 2013 Curriculum LKPD in increasing the learning independence of students themselves both internally and externally are consistency, creativity, lack of student focus, weak grasping power of students in understanding the material and distance learning in pandemic conditions. covid 2019. Keywords : LKPD, Independence, Pancasila Education and Citizenship